The Relationship Between Characteristics of Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (COPD) Hospitalized with Blood Eosinophil Levels at Waled Regional Hospital in September 2023-September 2024 - Jidni Alaya Suryadirezi; Dwi Rosa Eka Agustina; Isti Noviani (International Journal of Health and Pharmaceutical (IJHP), 2026)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disorder with persistent airflow limitation and prone to acute exacerbations, in which blood eosinophil levels have been proposed as a marker of type 2 inflammation and response to therapy. This study aimed to determine the relationship between clinical-demographic characteristics of patients with acute exacerbations of COPD hospitalized at Waled Regional Hospital and blood eosinophil levels during the period of September 2023–September 2024. This study was a quantitative observational analytical study with a cross-sectional design conducted on 132 inpatients with exacerbations of COPD who met the inclusion criteria based on medical records, including diagnosis, first-time blood eosinophil laboratory results, and the absence of active helminth infections. Data were collected retrospectively from medical records and analyzed using univariate descriptive statistics and Spearman's rank correlation test in SPSS. The results showed that 62.1% of patients were male, 68.9% were aged ≥60 years, 75.0% had normal eosinophils (0–300 cells/μL), and 25.0% had elevated eosinophils (>300 cells/μL). Statistical tests found a significant but weak association between male gender and blood eosinophil levels (p = 0.023, rs = 0.198), while no significant association was found between age or occupational history and eosinophil levels. The results showed that in this regional referral hospital setting, elevated eosinophils were more common in male patients with acute exacerbation of COPD, while age and occupation did not show a significant association. The conclusions of the study underscore the need for larger prospective studies to clarify the role of eosinophils as a marker of severity and response to therapy in low-middle-income areas.